Trimodality therapy and definitive chemoradiotherapy for esophageal cancer: a single-center experience and review of the literature. Issue 7 (1st October 2015) - Hategan, M.; Cook, N.; Prewett, S.; Hindmarsh, A.; Qian, W.; Gilligan, D.
Summary: In the UK, the standard of care for esophageal cancer has generally combined surgery with neoadjuvant chemotherapy, with definitive chemoradiotherapy (dCRT) being reserved for certain subgroups. Chemoradiotherapy followed by surgery (trimodality therapy) has not been widely adopted. The outcomes of patients undergoing dCRT or trimodality therapy at our cancer center between 2004 and 2012 were restrospectively analyzed. Trimodality therapy was offered to selected patients of good performance status (World Health Organisation performance status 0/1), with squamous cell carcinoma or bulky adenocarcinoma. dCRT was offered to patients of good PS but with comorbidities, upper third tumors or at patient's request. Patients received four cycles of chemotherapy with a platinum agent (mostly cisplatin) and a fluoropyrimidine (mostly 5-fluorouracil) over a total of 11 weeks. Cycles 3 and 4 were given concurrently with radiotherapy: 50 Gy in 25 fractions for dCRT and 45 Gy in 25 fractions in the trimodality group. Surgery occurred 8–10 weeks following the completion of chemoradiotherapy. The cut-off length for maximum gross tumor volume length was 10 cm. One hundred two patients were included (47 received dCRT, and 55 received trimodality treatment). The majority of tumors were stage III (80.4%), and two-thirds were located in the distal esophagus (64.7%). Median follow-up was 44 months. The 2-year overall survival (OS) was 57.3% (median OS 39.7 months) for the dCRT group and 77.8% (median not reached) for the trimodality group. The 5-year OS rates were 38% and 58%, respectively. Postoperative mortality rate was low at 1.8%, and the pathological complete response rate was 23.6%. In conclusion, trimodality treatment for patients with esophageal and junctional gastroesophageal tumors offers high rates of 2-year survival, and the potential for long-term cure. dCRT is an established alternative for patients that are not fit or suitable for surgery.